Exploring Mental Wellbeing Among Healthcare Workers In Saudi Arabia: A Narrative Review (Journal of Namibian Studies : History Politics Culture, 2022)
Healthcare workers encounter various stressful and demanding events during their daily routine. Constant interactions with patients suffering from different illnesses, increased working hours, workload, and other sociodemographic factors may cause mental distress among healthcare workers, especially those at the forefront of service delivery. The present narrative review explores the current state of knowledge on the factors affecting the mental wellbeing of healthcare workers in Saudi Arabia. Studies confirm the high prevalence of mental distress among healthcare workers, which manifests in different forms, including stress, trauma, burnout, turnover, and depression.  The mental health of workers in the health industry is critical, and effective mechanisms should be adopted to ensure continuous quality service delivery. Strategies outlined in the literature include improved communication, a favorable work environment, proper allocation of roles, constructive working relationships, exercise activities, consultations, and increased social support group interventions.